Cu2(OH)PO4/g-C3N4 composite as an efficient visible light-activated photo-Fenton photocatalyst. Issue 116 (5th November 2015) - Chen, Changhong; Zhou, Yan; Wang, Ningning; Cheng, Linyu; Ding, Hanming
Abstract : The synergistic effect of Cu2 (OH)PO4 /H2 O2 and g-C3 N4 highly boosts the catalytic activity towards photo-Fenton photocatalytic degradation of rhodamine B. Abstract : Novel Cu2 (OH)PO4 /g-C3 N4 composites with different mass percentages of Cu2 (OH)PO4 have been prepared successfully for the photo-Fenton photocatalytic process. By combining the Fenton reagent of Cu2 (OH)PO4 /H2 O2 with the photocatalyst of g-C3 N4, the Fenton reaction is highly accelerated with the aid of the photocatalytic process. The composite with 30% Cu2 (OH)PO4 shows the best photo-Fenton photocatalytic efficiency with a reaction rate constant of 0.093 min −1, which is about 12 and 2.4 times higher than that of pure Cu2 (OH)PO4 (0.0076 min −1 ) and pure g-C3 N4 (0.039 min −1 ) under the same conditions, respectively. Moreover, the Cu2 (OH)PO4 /g-C3 N4 composite is very stable and reusable. A possible photo-Fenton photocatalytic reaction mechanism for the Cu2 (OH)PO4 /g-C3 N4 composite was proposed based on the band structures of Cu2 (OH)PO4 and g-C3 N4 as well as the previous research results. We confirm that hydroxide radicals and holes play main roles during the photo-Fenton photocatalytic process. Above all, the Cu2 (OH)PO4 /g-C3 N4 composite as a stable, highly efficient, and economic photo-Fenton photocatalyst shows potential applications for the treatment of organic pollutants in wastewater.